2017
DOI: 10.1111/1744-9987.12567
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Earlobe Creases and Their Association With History of Cardiovascular Disease in Patients Undergoing Hemodialysis: A Cross‐Sectional Study

Abstract: Earlobe creases are surrogate markers for high risk of cardiovascular disease. There is no data concerning earlobe creases among hemodialysis patients, who have an increased risk of cardiovascular disease. A cross-sectional study was conducted to determine the prevalence of earlobe creases and their association with prevalent cardiovascular disease among hemodialysis patients. Patients undergoing hemodialysis were recruited from five outpatient hemodialysis centers. Both earlobes were photographed during a dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The presence of ELC, which can be assessed easily without any test, might function as a visible prompt for both physicians and patients to screen for CVD. We previously reported a cross-sectional study showing that the prevalence of ELC was not associated with prevalent CVD in Japanese hemodialysis patients (15). However, survivor bias may have affected the results of that study.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The presence of ELC, which can be assessed easily without any test, might function as a visible prompt for both physicians and patients to screen for CVD. We previously reported a cross-sectional study showing that the prevalence of ELC was not associated with prevalent CVD in Japanese hemodialysis patients (15). However, survivor bias may have affected the results of that study.…”
Section: Introductionmentioning
confidence: 89%
“…This study was conducted as a follow-up to a previously reported cross-sectional study (15); a detailed description of this cohort has been previously published. In brief, individuals undergoing hemodialysis were recruited from five outpatient hemodialysis centers in Niigata, Japan, between February and November 2012.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…No association with cardiac disease was found. Earlobe photos were examined independently of clinical data by two nephrologists …”
mentioning
confidence: 99%
“…Earlobe photos were examined independently of clinical data by two nephrologists. 18 Richard A. Sherman…”
mentioning
confidence: 99%